Pengaruh Kepemimpinan, Disiplin dan Motivasi Kerja Terhadap Kinerja Guru dan Karyawan SD Islam Al Adabul Muf’rod Kabupaten Bekasi - Mutia Rukmana Harahap (Pascasarjana STIE Amkop Makassar, 2026)
Human resource management (HRM) plays a strategic role in determining the success of educational institutions, as the quality of human resources is directly related to institutional performance. Based on the education report of SD Islam Al Adabul Mufrod, Bekasi Regency, several problems were identified, including unmet student enrollment targets, low learning quality, and weak consistency in implementing the school’s vision and mission. These conditions indicate the need to strengthen HR management, particularly in leadership, work discipline, and employee motivation.This study aims to analyze the influence of leadership (X1), work discipline (X2), and motivation (X3) on performance (Y). The research employed a quantitative approach with a population of 44 respondents, all of whom were included as the sample. Data were collected through validated questionnaires and analyzed using multiple linear regression.The findings show that leadership has a positive and significant effect on performance (B = 0.276; t = 2.987; p = 0.005). Work discipline (B = 0.238; t = 3.748; p = 0.001) and motivation (B = 0.412; t = 5.090; p = 0.000) also significantly influence performance overall results.